Sistem Informasi Penjualan, Pembelian Dan Jasa Grooming Pada Tera Petshop - Suwinarno Nadjamuddin (Jurnal Teknologi dan Informasi (JATI), 2014)
Tera is one Petshop Petshop in Bandung, which provides cat food, dog food, hamster food, cage, bags etc. In addition selling a variety of foods and accessories Tera pet shop also offer grooming services or known with animals salon especially for cats only, such as treatments, baths, and cut nails. But one of the problems faced is data processing is not computerized such as sales and purchasesdata processing, sales and purchasesreport making , cat grooming and inventory. With the computerized system or the proposed system. Tera pet shop can perform data processing more quickly, accurate, and efficient. Especially in the sales and purchaseprocessing.System approach usedthe structured method with the analysis tools are Flowmap, Context Diagram, and Data Flow Diagram. While the programming language used PHP and the database used MySQL database.Sales, Purchasing and Grooming Service Information System in Tera Petshop was built as one of the solutions of the problems faced by Tera Petshop with building an application that can simplydata processingfaster, and data required can also be betterstored and processed.